An Analysis of Flora Symbols in the Qur'an from the Perspective of Charles Sanders Peirce - Bahy, Moh. Buny Andaru; Syaifuddin, Helmi; Budiman Putra, Muhammad Fatih; Wakhid, Moh. Rizalul (TAFSE: Journal of Qur'anic Studies, 2024)
Symbols are important elements that are often used in everyday life. The Qur'an contains many messages which are depicted using certain symbols. The current reality is that there are still many who do not know and understand the symbols used in the Koran. This research will explore and discuss the use of flora symbols used in the Qur'an. These symbols are important to know and understand with the aim of understanding the messages contained in the Qur'an. This research uses a qualitative descriptive research type. Data analysis in this research uses the triangle meaning semiotic theory from Carles Sanders Peirce's perspective. After carrying out the analysis, this research found that there are 25 verses in the Qur'an that use flora symbols, which are divided into 2 classifications, namely general and specific symbol mention classifications. Which is divided into 3 general mentions of floral symbols and 7 specific mentions of floral symbols. The symbols mentioned are generally used in the Qur'an to show God's power and mercy in everything that has been created. Meanwhile, the Qur'an uses specific mention of flora symbols to show the benefits of flora in the continuity of human life.